2003
DOI: 10.1093/annonc/mdg339
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of pemetrexed in breast cancer patients pretreated with anthracyclines

Abstract: Our trial demonstrates pemetrexed to be active in breast cancer, with manageable toxicity. Activity of pemetrexed did not appear to be adversely affected by prior taxane, 5-fluorouracil or endocrine treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…The response rate was comparable to the 21% observed when 600 mg/m 2 of pemetrexed was given to patients with locally advanced or metastatic breast cancer, most of whom had one prior chemotherapy regimen (6). As expected, the vitamin supplementation included in this study greatly improved the pemetrexed safety profile over that observed by Martin et al (6).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The response rate was comparable to the 21% observed when 600 mg/m 2 of pemetrexed was given to patients with locally advanced or metastatic breast cancer, most of whom had one prior chemotherapy regimen (6). As expected, the vitamin supplementation included in this study greatly improved the pemetrexed safety profile over that observed by Martin et al (6).…”
Section: Discussionsupporting
confidence: 77%
“…For each patient, the P600 arm administered a mean of 6.1 cycles (median, 6; range, , and the P900 arm administered a mean of 6.0 cycles (median, 5; range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Both arms received a high percentage of the planned dose (P600 = 98.2%; P900 = 95.7%).…”
Section: Treatmentmentioning
confidence: 99%
“…Llombart-Cussac and colleagues observed response rates of 17 and 19% when pemetrexed was given at 600 and 900 mg/m 2 to MBC patients in the first-line setting on Day 1 of a 21-day cycle [25]. Earlier 21-day trials have shown response rates in anthracyclinerefractory groups (ORR 17%), anthracycline-failure groups (ORR 24%), anthracycline-and taxane-pretreated groups (ORR 26% and ORR 28%, respectively), and heavily pretreated groups who had received prior anthracycline, a taxane, and capecitabine (ORR 8%) [15,17,26]. In combination trials, pemetrexed with gemcitabine and pemetrexed with epirubicin produced response rates not dramatically different from those in trials using single-agent pemetrexed [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The drug has been recently approved for the treatment of inoperable malignant mesothelioma [3]; moreover, pemetrexed has been registered for the second-line treatment of locally advanced or metastatic non-small cell lung cancer, since it has shown comparable efficacy but a better toxicity profile compared to docetaxel [4]. In addition, pemetrexed has shown significant activity against a broad spectrum of solid tumors [5,6,7,8,9,10,11,12,13]. Pemetrexed has a favorable toxicity profile although its use is associated with myelosuppression, gastrointestinal toxicity, skin rash and mucositis [14, 15].…”
Section: Introductionmentioning
confidence: 99%